An alternative view on the ethics of synthetic biology: an Indian Hindu perspective - Varsha Aravind Paleri (Global Bioethics)
Synthetic Biology (SynBio) is a rapidly advancing interdisciplinary field that holds immense potential to address pressing global issues, including food insecurity, medical innovation, and environmental sustainability. Yet, the ethical discourse surrounding its development has often struggled to keep pace with its scientific progress. This stagnation, I argue, arises largely from the persistence of dualistic frameworks – such as “natural” versus “artificial” or “human” versus “machine” – that dominate bioethical inquiry. These dichotomies limit the scope of moral reflection and hinder the development of more holistic ethical frameworks. This paper seeks to reframe these debates by drawing upon the non-dualistic worldview of Sanātana Dharma, the foundation of Indian Hindu philosophy. Through this lens, I propose a different perspective that emphasizes interconnectedness, responsibility, and reverence for all forms of life, natural and synthetic alike, offering a more inclusive and holistic approach to evaluate emerging biotechnologies.